2011
DOI: 10.1371/journal.ppat.1002209
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Signature Patterns in HIV-1 B Clade Envelope Glycoproteins Associated with either Early or Chronic Infections

Abstract: Here we have identified HIV-1 B clade Envelope (Env) amino acid signatures from early in infection that may be favored at transmission, as well as patterns of recurrent mutation in chronic infection that may reflect common pathways of immune evasion. To accomplish this, we compared thousands of sequences derived by single genome amplification from several hundred individuals that were sampled either early in infection or were chronically infected. Samples were divided at the outset into hypothesis-forming and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
152
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 121 publications
6
152
0
Order By: Relevance
“…Several previous studies have observed that the transmitted virus is underglycosylated in an HIV-1 subtype C cohort (4) and in an HIV-1 subtype A cohort (19), although this effect was less apparent overall in a subtype B cohort (19,21,22), with the exception of underrepresentation of a glycosylation site at position 413 (24). We have been able to confirm this observation of reduced glycosylation of the transmitted virus in this large subtype C cohort (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several previous studies have observed that the transmitted virus is underglycosylated in an HIV-1 subtype C cohort (4) and in an HIV-1 subtype A cohort (19), although this effect was less apparent overall in a subtype B cohort (19,21,22), with the exception of underrepresentation of a glycosylation site at position 413 (24). We have been able to confirm this observation of reduced glycosylation of the transmitted virus in this large subtype C cohort (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In several studies, there has been consistent observation of reduced length of the variable regions in the Env protein and/or reduced N-linked glycosylation density of the Env protein, features reported for subtypes C, A, and D HIV-1 (4,19,20) but less clear for subtype B HIV-1 (19,21,22). An analysis of a large data set of subtype B env sequences revealed in the transmitted viruses selection for a basic amino acid at position 12 in the Env leader sequence that increases Env density on virions and underrepresentation of a glycosylation site at codon 413 (23,24), although this site is typically not present in subtype C HIV-1. It has been reported that the reduced glycosylation of the Env protein of transmitted viruses enhances binding to ␣4␤7 integrin associated with CD4 ϩ T cells found in gut-associated lymphoid tissue and impacts Env conformation and the interaction with CD4 (25), although this relationship was not detected in a larger sampling of transmitted viruses (13).…”
mentioning
confidence: 99%
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, within-host HIV-1 evolution in response to antiretroviral (61,72), host cellular immune (15,50,71,94,95), antibody (46), and vaccine-induced (103) selection pressures occurs along generally predictable mutational pathways (3,84). Studying these evolutionary pathways can offer insight into the immunopathogenesis of HIV-1 and may help inform the design of immune-based interventions and vaccines.…”
mentioning
confidence: 99%